Isolasi, Identifikasi, dan Serotyping Avibacterium paragallinarum dari Ayam Petelur Komersial yang Menunjukkan Gejala Snot - Elisabet Tangkonda; Charles Rangga Tabbu; Agnesia Endang Tri Hastuti Wahyuni (Jurnal Sain Veteriner, 2019)
Infectious coryza (snot) is one of acute respiratory disease in breeders, layers, and broilers caused by Avibacterium paragallinarum (Av. paragallinarum). This disease is very harmful because of its cause decrease in egg production and high morbidity. Snot incident in Indonesia still is reported. Vaccination is one of the best preventive measures, but reports about Av. paragallinarum serotype at the field so lack so that the correspondence between serotype Av. paragallinarum in the field to those used for vaccination is unknown. Av. paragallinarum has strains with different antigenicity and until now known three serotypes there are serotypes A, B and C. Serotypes A and C are pathogenic then serotypes B. The purpose of this study was to isolate, identify and to determine the serotype of Av. paragallinarum from the commercial layer that showing symptoms of snot. Samples were taken from layer which showed symptoms of snot (nasal foul smelling exudate, infra-orbital and wattle swelling, conjunctivitis, and snoring) from some layer farms. Samples were cultured on chocolate agar and then incubated in a candle jar at 37 ᴼC for 18-24 hours. Bacteria colony and cell morphology were observed and performed biochemical tests (catalase, oxidase, urease, indole, and fermentation of carbohydrates) in suspected colonies. Serotypes test was conducted using plate agglutination test (PAT). This study revealed 4 isolates Av. paragallinarum with 2 isolates are serotype B and 2 other are serotype C.